Advances in lipid-based nanocarriers for breast cancer metastasis treatment - Joun, Ingrid; Nixdorf, Sheri; Deng, Wei (Frontiers in Medical Technology, 2022)
Breast cancer (BC) is the most common cancer affecting women worldwide, with over 2 million women diagnosed every year, and close to 8 million women currently alive following a diagnosis of BC in the last 5-years. The side effects such as chemodrug toxicity to healthy tissues and drug resistance severely affect the quality of life of BC patients. To overcome these limitations, many efforts have been made to develop nanomaterial-based drug delivery systems. Among these nanocarriers, lipid-based delivery platforms represented one of the most successful candidates for cancer therapy, improving the safety profile and therapeutic efficacy of encapsulated drugs. In this review we will mainly discuss and summarize the recent advances in such delivery systems for BC metastasis treatment, with a particular focus on targeting the common metastatic sites in bone, brain and lung. We will also provide our perspectives on lipid-based nanocarrier development for future clinical translation.